2019
DOI: 10.18494/sam.2019.2502
|View full text |Cite
|
Sign up to set email alerts
|

Application of Supercapacitors in Photovoltaic Power Generation System

Abstract: In view of the intermittent and unstable output voltage of the photovoltaic power generation module, a supercapacitor is designed as the control system to improve the power quality and power supply continuity of the photovoltaic power generation system. The whole circuit includes a maximum power point tracking converter, a boost converter, a Hall element, a waveform recorder, and a supercapacitor bank. Because the output current of each solar photovoltaic module is very important for the control of the solar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Wu et al proposed a supercapacitor as a control system and a sensing circuit for accurately detecting the output current and current change rate of solar power generation systems to solve the problem of indirection and instability of the output voltage of PPG modules. The experimental results showed that the control system can effectively suppress the output voltage fluctuation of the PPG module and enhance the reliability of load power consumption [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al proposed a supercapacitor as a control system and a sensing circuit for accurately detecting the output current and current change rate of solar power generation systems to solve the problem of indirection and instability of the output voltage of PPG modules. The experimental results showed that the control system can effectively suppress the output voltage fluctuation of the PPG module and enhance the reliability of load power consumption [12].…”
Section: Related Workmentioning
confidence: 99%
“…The os in Equation ( 11) is the subscript of the globally optimal position particle. The evolution of i under dimension j is shown in Equation (12).…”
Section: Construction Of the Mppt Control Algorithm Based On Hqpsomentioning
confidence: 99%